2022
DOI: 10.1038/s41467-022-30459-5
|View full text |Cite
|
Sign up to set email alerts
|

A deep learning model and human-machine fusion for prediction of EBV-associated gastric cancer from histopathology

Abstract: Epstein–Barr virus-associated gastric cancer (EBVaGC) shows a robust response to immune checkpoint inhibitors. Therefore, a cost-efficient and accessible tool is needed for discriminating EBV status in patients with gastric cancer. Here we introduce a deep convolutional neural network called EBVNet and its fusion with pathologists for predicting EBVaGC from histopathology. The EBVNet yields an averaged area under the receiver operating curve (AUROC) of 0.969 from the internal cross validation, an AUROC of 0.94… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…Of the studies with weakly supervised learning, Muti et al reported a comparable performance with an AUROC of 0.859 on the external dataset. However, the results of these previous studies elucidate that supervised learning approaches, where the model was trained on tumor patches, outperformed the weakly supervised approach with an AUROC of 0.941 29 .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Of the studies with weakly supervised learning, Muti et al reported a comparable performance with an AUROC of 0.859 on the external dataset. However, the results of these previous studies elucidate that supervised learning approaches, where the model was trained on tumor patches, outperformed the weakly supervised approach with an AUROC of 0.941 29 .…”
Section: Discussionmentioning
confidence: 98%
“…Until now, seven studies on EBV status prediction via a deep learning approach using digitalized WSIs have been published (Supplementary Table S1 ) 25 31 . Of these, the most similar to our pipeline are those proposed by Zhang et al and Zheng et al 28 , 29 ; in these two previous studies, a two-step approach utilizing a tumor classifier and an EBV classifier was implemented. Most studies have trained EBV classifiers using tumor patches generated from tumor annotation, with 28 , 29 or without 25 – 27 training tumor classifiers—a tumor annotation-based approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the field of medical image classification, deep learning algorithms are the most effective algorithms, and Convolutional Neural Network (CNN) is a widely used model for image classification, which can extract information from original medical images and classify normal and abnormal case images ( 17 ). Recently, Visual Transformer, which is originally applied to Natural Language Processing tasks, have become popular in computer vision, and Vision Transformer (ViT) have effective classification results when trained on large amounts of data and can significantly reduce the computer hardware and software resources required for training ( 18 ).…”
Section: Introductionmentioning
confidence: 99%